Fundamentals and mechanisms of national legislation on the prevention of stalking violation of personal space - Ordayeva А.Ж.; Shekerbekova М.С.; Abutaeva С.Б. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
In this research article, a study of the bases and mechanisms of national legislation on the prevention of stalking (tracking) violation of a person’s personal space was carried out. The purpose of the scientific research is to provide a comparative legal analysis of the national legislation on the prevention of violation of the personal space of a person with foreign legislation, and to improve the national legislation on the prevention of violation of a person’s personal space. As a result of the discussion of the laws of far and near foreign countries and the comparative legal analysis of the national legislation on the prevention of stalking (tracking) violation of a person’s personal space, a set of separate recommendations was made. Also, in order to determine the legal bases and practical mechanisms of protection of individuals from the crime of stalking (tracking) according to the international legal system, the result of the differentiation of the system of law enforcement and judicial bodies’ actions on the protection of individuals from the crime of stalking (tracking) in the Republic of Kazakhstan defined. In addition, Stalking (tracking) proposed national legislation frameworks and mechanisms to prevent violation of personal space.